2018
DOI: 10.1002/jnr.24241
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and management of glaucoma associated with phakomatoses

Abstract: The phakomatoses, encephalotrigeminal angiomatosis (ETA; Sturge-Weber Syndrome), neurofibromatosis type 1 (NF1 or von Recklinghausen disease), Von Hippel-Lindau (VHL) disease, tuberous sclerosis (TSC), oculodermal melanocytosis (ODM), and phakomatosis pigmentovascularis are a group of neurocutaneous disorders that have characteristic systemic and ocular manifestations. Through many different mechanisms, they may cause glaucomatous damage of the optic nerve and subsequent vision loss varying from mild to severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 82 publications
(143 reference statements)
0
9
0
2
Order By: Relevance
“… 2 Ipsilateral congenital glaucoma is present in 23–50% of NF-1 patients with eyelid plexiform neurofibromas. 2 , 3 , 6 Various mechanisms for IOP elevation have been implicated including infiltration of the anterior chamber angle by neurofibroma cells, PAS formation in association with ectropion uveae, and other angle abnormalities such as the presence of an anterior and flat iris insertion, abundant iris processes, or increased pigmentation of the angle. 3 , 6 , 8 , 9…”
Section: Discussionmentioning
confidence: 99%
“… 2 Ipsilateral congenital glaucoma is present in 23–50% of NF-1 patients with eyelid plexiform neurofibromas. 2 , 3 , 6 Various mechanisms for IOP elevation have been implicated including infiltration of the anterior chamber angle by neurofibroma cells, PAS formation in association with ectropion uveae, and other angle abnormalities such as the presence of an anterior and flat iris insertion, abundant iris processes, or increased pigmentation of the angle. 3 , 6 , 8 , 9…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma has been found to occur in about 1 in 300 NF-1 patients [5]. Patients with orbito-facial involvement have been linked to higher rates of glaucoma at 23-50% [6][7][8]. It was also found that patients with eyelid plexiform neurofibromas have ipsilateral globe enlargement up to 36 mm axial length [6].…”
Section: Glaucomamentioning
confidence: 99%
“…The most commonly described mechanism is the presence of neurofibromas in the angle causing aqueous outflow obstruction [6]. Other suggested processes include secondary angle closure due to the anterior displacement of the peripheral iris by an abnormally thickened ciliary body or developmental anomalies in the angle [7].…”
Section: Glaucomamentioning
confidence: 99%
“…Nörofibromatoziste glokom hastaları pleksiform nörofibromlar ve ektropiyon üvea ile sık birliktelik gösterdiği için bu bulguların ortaya konması glokom açısından sıkı takip gerektirir. 26 Glokom eşlik eden hastaların prognozu genellikle kötüdür ve sıklıkla cerrahi tedavi gerektirir. Morales ve ark.nın, 13 hastalık NF ve glokom serisinde, tüm hastalara cerrahi gerekmiştir.…”
unclassified
“…27 Von Hippel Lindau (VHL) ve tuberoskleroza ise nadiren NVG hastalarının eşlik ettiği literatürde bildirilmiştir. 26 İntraoküler tümörlerde, tümöre bağlı vitreus hemorajisi, tedavi veya biyopsi örnekleri alınırken ortaya çıkan hemorajiler nedeni ile hemorajik glokom sık olarak görülebilmektedir. Glokom ilk haftalarda ortaya çıkarsa hemolitik karakterde iken, eğer hemorajiden aylar sonra ortaya çıkarsa hayalet hücreler nedeni ile olduğu düşünülmelidir.…”
unclassified